Correspondence between Éamonn Duggan and his fiancée May Kavanagh, written during his imprisonment after the Easter Rising - Duggan, Éamonn, 1874-1936; Duggan, May; Duggan, Cissie (1916)
Duggan's letters, written from Mountjoy, Portland and Lewes prisons, refer to his court martial following his participation in the Easter Rising, his health and morale during his imprisonment, the importance of receiving letters from home, his friendships with fellow republican prisoners notably Gerard Crofts, his progress in learning Irish, religious observance in prison and prospects for release. Some of his letters are partially blocked by the prison censors.
Kavanagh writes of her life in Dublin, her work, meetings with his family and their mutual friends and participation in events held to mark the first anniversary of the Rising. Her letters also include notes to Duggan from his friends and family, notably his sister Cissie Duggan.
Duggan was a member of the Irish Volunteers and fought at the North Dublin Union and later Fr. Mathew Hall during the Easter Rising.
Keywords: Duggan, Éamonn, -- 1874-1936; Ireland -- History -- Easter Rising, 1916 -- Prisoners and prisons